Evaluation of Recently Developed Regression Equation with Direct Measurement of Low-density Lipoprotein Cholesterol in a Bangladeshi Population (Journal of Enam Medical College, 2015)
Background: Meaningful underestimation of low-density lipoprotein (LDL) cholesterol is an important shortcoming of Friedewalds formula (FF) at higher triglyceride (TG) levels. Recently a regression equation (RE) has been developed using lipid profiles in one setting and validated externally for the calculation of LDL cholesterol. This newly developed RE requires more studies in different settings.Objective: The aim of this study was to evaluate the performance of the regression equation against direct measurement.Materials and Methods: Lipid profiles of 600 subjects attending a tertiary healthcare center were included in this study. Specimens were collected and lipid profiles were measured by standard methods. Sixty two lipid profiles with TG above 400 mg/dL were excluded. Calculated LDL cholesterol values using FF and RE were compared with measured LDL cholesterol by Pearsons correlation test, Passing & Bablok regression, accuracy within ±5% and ±12% of measured LDL cholesterol and two-tailed paired t test at various TG ranges.Results: The mean value of LDL cholesterol was 148.6 ± 37.2 mg/dL for direct measurement, 146.9 ± 42.4 mg/dL for FF and 148.6 ± 34.7 mg/dL for RE. The correlation coefficients of calculated LDL cholesterol values with measured LDL cholesterol were 0.949 (p